O48: MYOFERLIN: A NOVEL PREDICTIVE BIOMARKER AND THERAPEUTIC TARGET IN ADVANCED COLORECTAL CANCER. (27th April 2021) - Fowler, H; Sutton, P; Bowden, D; Parsons, J; Vimalachandran, D
Abstract: Introduction: Myoferlin is a protein involved in cell proliferation, migration and angiogenesis, which are essential in tumour metastasis. Its expression correlates with a poorer prognosis in various epithelial cancers, but has yet to be associated with survival in colorectal cancer. We aim to investigate myoferlin's role in cell migration, and the development of metastases in our patients with rectal cancer. Method: Tissue Microarrays (TMAs) of matched tumour and lymph node samples from 111 patients with rectal cancer were stained for myoferlin. Expression profiles were examined and correlated with clinical outcomes. Wound healing assays were used to assess the rate of migration in immortalised colorectal cells (HCT116, HT29) following myoferlin knockdown with siRNA. Result: Our TMAs demonstrated that high myoferlin expression in rectal tumour samples was associated with metastatic spread to local lymph nodes (p<0.05). Positive lymph nodes had significantly higher levels of myoferlin than non-involved lymph nodes (p<0.001). The positive predictive value (PPV) of a highly expressing lymph node containing metastatic spread was 100%, negative predictive value (NPV) 88.41%, 95% CI [80.81, 93.24]. Wound healing assays demonstrated a decreased ability of cells to migrate following myoferlin knockdown with siRNA, compared to controls (p<0.05). Conclusion: Our results demonstrate that high myoferlin expression is associated with metastatic spread to local lymph nodes, and increased migration and proliferation of cells. It is a predictor of poor clinical outcomes, and therefore warrants further investigation as a potential therapeutic target in both locally advanced and metastatic rectal cancer. Take-home message: We have demonstrated that the protein myoferlin is associated with metastatic spread of rectal cancer to local lymph nodes. Therefore it is a potential predictive biomarker and therapeutic target in advanced rectal cancer.